2001
DOI: 10.1128/jb.183.12.3663-3679.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization and Evolutionary Implications of a car Gene Cluster in the Carbazole Degrader Pseudomonas sp. Strain CA10

Abstract: The nucleotide sequences of the 27,939-bp-long upstream and 9,448-bp-long downstream regions of the carAaAaBaBbCAc(ORF7)Ad genes of carbazole-degrading Pseudomonas sp. strain CA10 were determined. Thirty-two open reading frames (ORFs) were identified, and the car gene cluster was consequently revealed to consist of 10 genes (carAaAaBaBbCAcAdDFE) encoding the enzymes for the three-step conversion of carbazole to anthranilate and the degradation of 2-hydroxypenta-2,4-dienoate. The high identities (68 to 83%) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
131
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(132 citation statements)
references
References 63 publications
0
131
0
1
Order By: Relevance
“…In addition, antABC gene encoding anthranilate 1,2-dioxygenase was found in the 21-kb region upstream from carAa ( Fig. 5a) (Nojiri et al 2001). This anthranilate degradative gene cluster is a putative composite transposon flanked by two homologous insertion sequences ISPre1 and ISPre2.…”
Section: Pseudomonas-type Car Gene Clustermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, antABC gene encoding anthranilate 1,2-dioxygenase was found in the 21-kb region upstream from carAa ( Fig. 5a) (Nojiri et al 2001). This anthranilate degradative gene cluster is a putative composite transposon flanked by two homologous insertion sequences ISPre1 and ISPre2.…”
Section: Pseudomonas-type Car Gene Clustermentioning
confidence: 99%
“…Enzymes designations: CarAaAcAd, carbazole 1,9a-dioxygenase; CarBaBb, 2 0 -aminobiphenyl-2,3-diol 1,2-dioxygenase; CarC, 2-hydroxy-6-oxo-6-(2 0 -aminophenyl)-hexa-2,4-dienoate hydrolase; CarD, 2-hydroxypenta-2,4-dienoate hydratase; CarE, 4-hydroxy-2-oxovalerate aldolase; CarF, acetaldehyde dehydrogenase (acylating); AntABC, anthranilate 1,2-dioxygenase; CatA, catechol 1,2-dioxygenase; CatB, cis,cis-muconate lactonizing enzyme; CatC, muconolactone d-isomerase. Compounds: I, CAR; II, 2 0 -aminobiphenyl-2,3-diol; III, 2-hydroxy-6-oxo-6-(2 0 -aminophenyl)-hexa-2,4-dienoate; IV, anthranilic acid; V, catechol; VI, cis,cis-muconate; VII, muconolactone; VIII, b-ketoadipic acid enol-lactone; IX, 2-hydroxy-penta-2,4-dienoate; X, 4-hydroxy-2-oxovalerate; XI, pyruvate; XII, acetaldehyde; XIII, acetyl coenzyme A (Nojiri et al 2001) strain SL1, Pseudomonas sp. strain SL4 and Microbacterium esteraromaticum strain SL6, produce anthranilic acid and catechol as the major metabolites of carbazole angular dioxygenation.…”
Section: Angular Dioxygenation Of Carbazolementioning
confidence: 99%
“…In fact, the car gene cluster of CA10 is located on circular plasmid pCAR1. 51) We isolated pCAR1 from CA10 that had been preserved as a glycerol stock since its isolation in 1993. Its entire nucleotide sequence was determined in 2003 to elucidate the mechanism by which the car gene cluster might be distributed in nature.…”
Section: Sequencing Of Plasmid Pcar1mentioning
confidence: 99%
“…As the molecular mechanism for adaptation, gene recruitment is the key to establish several simultaneous degradation activities and the entire catabolic capacity for the xenobiotics to which microorganisms are exposed [13]. It is reported that some bacterial strains have the capacity to metabolize carbazole.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that some bacterial strains have the capacity to metabolize carbazole. Therefore, Pseudomonas resinovorans CA10 has been widely studied [13,15,16]. So far, these different species of carbazole degraders all appear to follow a similar carbazole degradation pathway that begins with the oxidative cleavage of the heterocyclic nitrogen ring of carbazole to form 2 0 -aminobiphenyl-2, 3-diol.…”
Section: Introductionmentioning
confidence: 99%